2023
DOI: 10.1002/ijc.34503
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint associations of general and abdominal obesity with the risk of conventional adenomas and serrated polyps: A large population‐based study in East Asia

Abstract: Evidence regarding associations of general and abdominal obesity with the risk of conventional adenomas (ADs) and serrated polyps (SPs) from Asian population is scarce. Our study aimed to investigate the independent and joint associations of general obesity assessed by body mass index (BMI) and abdominal obesity assessed by waist circumference (WC) or waist-to-hip ratio (WHR) with the risk of ADs and SPs among 25 222 participants recruited by a population-based screening program. Compared to participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In addition to general obesity assessed by BMI, we may need to pay more attention to abdominal obesity assessed by waist circle conference or waist to hip ratio in future studies. 36,37 In addition, lifestyle factors 38 (Western diet, 39 alcohol, 40 tobacco, 41 prolonged sedentary TV viewing, 42 etc.) are risk factors for EOCRC or ACN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to general obesity assessed by BMI, we may need to pay more attention to abdominal obesity assessed by waist circle conference or waist to hip ratio in future studies. 36,37 In addition, lifestyle factors 38 (Western diet, 39 alcohol, 40 tobacco, 41 prolonged sedentary TV viewing, 42 etc.) are risk factors for EOCRC or ACN.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies in the BMI results may be attributed to the inconsistent composition of BMI categories across different screening protocols, and the predominantly cross‐sectional nature of the studies, which only observe BMI at the time of screening and lack longitudinal follow‐up. In addition to general obesity assessed by BMI, we may need to pay more attention to abdominal obesity assessed by waist circle conference or waist to hip ratio in future studies 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Bai et al demonstrated an association between WHR and conventional adenomas or serrated polyps. 39 Another study has indicated that men with a higher BMI and WHR are associated with an increased risk of hyperplastic polyps, adenomas, and the occurrence of both types of polyps. 40 The prevalence of colorectal diverticula was higher in overweight people, so the chance of the development of polyps increased with increasing BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Their gender-specific stratified analysis further suggested a more substantial positive association between SMD adherence and obesity risk in males compared to females ( 51 ). Considering that obesity is a significant risk factor for colorectal cancer and adenoma ( 52 , 53 ), the variation in the association between obesity and adherence to the SMD pattern across genders may be the reason why the association between SMD and colorectal adenoma risk is more significant in males.…”
Section: Discussionmentioning
confidence: 99%
“…Hazard ratios was adjusted for age, sex, race, education levels, smoking status, pack-years of smoking, BMI, aspirin use, history of hypertension, history of diabetes, family history of colorectal cancer, total energy intake, history of diverticulitis or diverticulosis, history of colonoscopy in past 3 years, and physical activity level. cancer and adenoma (52,53), the variation in the association between obesity and adherence to the SMD pattern across genders may be the reason why the association between SMD and colorectal adenoma risk is more significant in males.…”
Section: Discussionmentioning
confidence: 99%